Is Breath Best? A Systematic Review on the Accuracy and Utility of Nanotechnology Based Breath Analysis of Ketones in Type 1 Diabetes - Kamal Marfatia; Jing Ni; Veronica Preda; Noushin Nasiri (Biosensors)
Timely ketone detection in patients with type 1 diabetes mellitus (T1DM) is critical for the effective management of diabetic ketoacidosis (DKA). This systematic review evaluates the current literature on breath-based analysis for ketone detection in T1DM, highlighting nanotechnology as a potential for a non-invasive alternative to blood-based ketone measurements. A comprehensive search across 5 databases identified 11 studies meeting inclusion criteria, showcasing various breath analysis techniques, such as semiconducting gas sensors, colorimetry, and nanoparticle-based chemo-resistive sensors. These studies report high sensitivity and correlation between breath acetone (BrAce) levels and blood ketones, with some demonstrating accuracies up to 94.7% and correlations reaching R2 values as high as 0.98. However, significant heterogeneity in methodologies and cut-off values limits device comparability and precludes meta-analysis. Despite these challenges, the findings indicate that BrAce monitoring could offer significant clinical benefits by enabling the earlier detection of ketone buildup, reducing DKA-related hospitalisations and healthcare costs. Standardising BrAce measurement techniques and sensitivity thresholds is essential to broaden clinical adoption. This review underscores the promise of nanotechnology-based breath analysis as a transformative tool for DKA management, with potential utility across varied ketotic conditions.